Expanding the repertoire of deadenylases. Issue 10 (3rd October 2017) - Skeparnias, Ilias; Αnastasakis, Dimitrios; Shaukat, Athanasios-Nasir; Grafanaki, Katerina; Stathopoulos, Constantinos
ABSTRACT: Deadenylases belong to an expanding family of exoribonucleases involved mainly in mRNA stability and turnover, with the exception of PARN which has additional roles in the biogenesis of several important non-coding RNAs, including miRNAs and piRNAs. Recently, PARN in C. elegans and its homolog PNLDC1 in B. mori were reported as the elusive trimmers mediating piRNA biogenesis. In addition, characterization of mammalian PNLDC1 in comparison to PARN, showed that is specifically expressed in embryonic stem and germ cells, as well as during early embryo development. Moreover, its expression is correlated with epigenetic events mediated by the de novo DNMT3b methyltransferase and knockdown in stem cells upregulates important genes that regulate multipotency. The recent data suggest that at least some new deadenylases may have expanded roles in cell metabolism as regulators of gene expression, through mRNA deadenylation, ncRNAs biogenesis and ncRNA-mediated mRNA targeting, linking essential mechanisms that regulate epigenetic control and transition events during differentiation. The possible roles of mammalian PNLDC1 along those dynamic networks are discussed in the light of new extremely important findings.